2021
DOI: 10.2355/isijinternational.isijint-2020-353
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reactions and Inclusion Formations at an Early Stage of FeNb Alloy Additions to Molten Iron

Abstract: Nb is an important microalloying element in steelmaking. Its interaction with liquid Fe during an early stage of the alloying process has a considerable influence on the Nb recovery. In the present work, the inclusions in FeNb alloys were characterized using the electrolytic extraction method combined with SEM-EDS. The interfacial reactions between FeNb alloy and liquid Fe, as well as inclusion formations, were studied during an early stage of an alloy addition using a liquid-metal-suction method. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies have reported this kind of phenomenon. [20,56,57] Moreover, the temperature in the local area surrounding the alloy will decrease to a certain extent. As a result, TiN inclusions can form inside this area due to the increase of the supersaturation degree caused by the temperature drop.…”
Section: Evolution Mechanism Of the Inclusions In Steelmentioning
confidence: 99%
“…Previous studies have reported this kind of phenomenon. [20,56,57] Moreover, the temperature in the local area surrounding the alloy will decrease to a certain extent. As a result, TiN inclusions can form inside this area due to the increase of the supersaturation degree caused by the temperature drop.…”
Section: Evolution Mechanism Of the Inclusions In Steelmentioning
confidence: 99%
“…It means that they were not significantly melted or dissolved, which was similar to what was found for FeNb alloys. [9] On the contrary, the LCFeCr alloy was melted since their sizes decreased significantly, which is discussed in detail later. According to the Fe-Cr-C phase diagram calculated using Factsage 7.2 with databases of FactPS and FSstel (Figure 4), the approximate melting point of the investigated HCFeCr alloy is above 1873 K (1600°C), which indicates that the alloy piece cannot melt at the given experimental conditions.…”
Section: B Macroscopic Observations Of the Qt Samplesmentioning
confidence: 99%
“…[5] Several researchers have investigated the early stage dissolution behavior of different ferroalloys. [4,[6][7][8][9] However, not enough attention has been paid to the interfacial processes between FeCr alloys and liquid iron and steel so far. In stainless steelmaking process, comparatively cheap HCFeCr alloys are added initially before decarburization.…”
Section: Introductionmentioning
confidence: 99%